Optimizing Ocean Energy Harvesting: The Significance of Natural Frequency in Piezoelectric Generator Device Electrical Output - Ede Mehta Wardhana; Meitha Soetardjo; Semin Semin; Agoes Santoso; Sutopo Purwono Fitri (International Journal of Marine Engineering Innovation and Research, 2023)
This study explores the significance of the natural frequency parameter in enhancing the electrical performance of a piezoelectric generator device, mainly when deployed in ocean energy harvesting. While natural energy harvesting aims to establish affordable and sustainable renewable energy sources, piezoelectric devices capitalize on the inherent piezoelectric effect derived from natural movements. Despite the abundance of constant natural movements in the Earth's environment, the application of piezoelectric devices in ocean energy remains relatively understudied. The experimental setup involves a cantilever-designed piezoelectric device made from polyvinylidene fluoride (PVDF). The study investigates the relationships between vibration frequency, initial distance, and electrical output. Findings indicate that higher setup parameters may lead to increased electrical output, but the relationship is not linear. Notably, the resonance between the vibration frequency and the device's natural frequency emerges as a critical factor in optimizing electrical performance. Detailed experimentation, visualized through figures and graphs, demonstrates the nuanced interplay of setup parameters and electrical output. The study emphasizes that the initial distance, while important, does not singularly determine the device's electrical performance. It challenges conventional beliefs by showcasing that piezoelectric devices can operate efficiently in tight spaces. Furthermore, the study delves into the non-linear relationship between vibration frequency and electrical output. Examining natural and resonant frequencies reveals that resonance occurs most prominently at the device's natural frequency, emphasizing the importance of precise tuning for optimal performance. The findings offer valuable insights for the strategic deployment of piezoelectric technology in ocean energy harvesting, paving the way for more efficient and effective devices in real-world conditions